Программа для установления переводных эквивалентов Treq: преимущества и недостатки - Charciarek, Andrzej (Studia Rossica Posnaniensia, 2020)
The article presents how the Treq corpus tool can be used in translation and lexicography. It also provides a description of Polish, Czech and Russian text resources found in the Interpcorp parallel corpus as well as Treq features. Furthermore, the article provides specific examples illustrating how the Treq application can be used in Polish-Czech and Russian-Czech translation lexicography. The author uses samples of translation including single and multi-word units in order to show benefits and shortcomings of the Treq application.